The Giving Variation of Concentration Kecombrang Flowers Extract (Etlingera elatior Jack R. M. Sm) as Natural Insectiside Against Aedes spp - Lia Andriani Tarigan; Ridwanti Batubara; Sumardi Sumardi (Program studi Kehutanan USU, 2014)
Aedes spp have been public health problems, such as dengue, yellow fever, chikungunya and others. The use of chemical insecticides make toxic effects in humans and environment. Therefore, the necessary existence of alternative insecticides that are safer for the environment. One of that is considered as natural insecticide is kecombrang (Etlingera elatior Jack R. M. Sm) flowers. The purpose of this research is to prove that kecombrang flowers extract has potential as an insecticide against Aedes spp. This research is a laboratorial experimental research with true experimental post test only control group design. The repetitions were done three times with four types of solutions which are, control (aquades), and kecombrang extracts 3%, 4.5%, 6%. Every repetitions were perceived at 3 intervals 10 minutes, 20 minutes , 30 minutes. Mortality of Aedes spp seen after 24th hours. From the One Way ANOVA test found significant differences in each flower extract concentration effect kecombrang Based on the result of this research, it is conclude that extract of kecombrang flowers have a potential as an insecticide against Aedes spp and effective in 4.5 % concentrate.Key words: Kecombrang, extract, aedes spp, natural insectiside